Deservingness, Conditionality and Public Perceptions of Work Disability: The Influence of Economic Inequality. (August 2022) - Ciccia, Rossella; French, Declan; Kee, Frank; O'Doherty, Mark
This article contributes to classical debates about the role of self-interest and social norms in shaping the moral economy of work and welfare by incorporating economic inequalities in the analysis of opinions about welfare deservingness. The relationship between inequality and perceptions of work conditionality has received little attention in previous studies. This article addresses this issue by investigating the association between economic inequalities and perceived work limitations of disabled people experiencing various conditions related to health using vignettes from the English Longitudinal Study of Ageing. The results show that people living in areas with higher levels of wealth inequality, but not income inequality, were more likely to rate the vignettes as limited in the amount of work that individuals can do due to health problems. This finding casts doubts on the crucial role attributed to self-interest as the central mechanism linking economic inequality and solidaristic, pro-welfare attitudes.